The Sustainable Development Goals: a plan for building a better world? - Pogge, Thomas (Journal of global ethics, 2015)
Despite some clear positives, the draft text of the Sustainable Development Goals does not fulfill its self-proclaimed purpose of inspiring and guiding a concerted international effort to eradicate severe poverty everywhere in all of its forms. We offer some critical comments on the proposed agreement and suggest 10 ways to embolden the goals and amplify their appeal and moral power. While it may well be true that the world's poor are better off today than their predecessors were decades or centuries ago, to judge whether this is moral progress, we must bring into view what was possible then and what is possible now. We may well find that there have never been so many people avoidably subjected to life-threatening deprivations as there are today, and if this is the case, we should insist that our governments end this oppression immediately through appropriate institutional reforms to be prominently outlined in their post-2015 agenda.